اردو تفسیری ادب میں اجتہادی رجحانات: ایک تجزیاتی مطالعہ: Ijtihadi Trends in Urdu Exegetical Literature: An Analytical Perspective - Arshad, Fouzia; Munawar Cheema, Prof. Dr. (Al-Amīr Research Journal for Islamic Studies, 2024)
The Creator of humanity designated the first human as His vicegerent and Prophet, initiating a continuous process of divine guidance. Although the chain of Prophethood concluded with the final Prophet ﷺ, divine guidance persists eternally through the Qur’an and Sunnah. With the passage of time, new social, economic, and political challenges arise, necessitating the application of ijtihad. Individual ijtihad refers to scholars addressing such issues independently, whereas collective ijtihad involves a collaborative effort by jurists to derive solutions based on Shariah principles. The core purpose of Qur’anic exegesis is to communicate the Qur’an’s eternal message to the people of each era in a manner that resonates with their contemporary realities. Urdu exegetical literature plays a significant role in addressing emerging issues, ensuring that individuals and societies comprehend the Qur’an as a dynamic source of guidance for personal and collective challenges. This literature underscores the relevance of the Qur’an, presenting it as a timeless book capable of addressing the evolving needs of humanity. This study critically examines how ijtihadi trends have been integrated into Urdu exegesis to make the Qur’an accessible and relevant in addressing modern issues. Keywords: Ijtihad, Qur’anic Exegesis, Urdu Literature, Tafsir, Collective Ijtihad, Social Challenges, Islamic Guidance, Contemporary Issues